Use of asymmetric PCR to generate long primers and single-stranded DNA for incorporating cross-linking analogs into specific sites in a DNA probe. - Wooddell, C I; Burgess, R R

(untitled) (Genome Research, 1996)
Photoactivatable DNA analogs have been incorporated enzymatically into DNA and used to map the locations of polypeptides in protein complexes bound to DNA. We have developed a procedure for generating long primers from short oligodeoxyribonucleotides (oligos) to incorporate DNA cross-linkers at specific sites within either strand of DNA probes of < or = 206 bp. Single-stranded DNA molecules of 52-206 nucleotides in length were generated by asymmetric polymerase chain reactions (aPCR), using an excess of one short sense-strand primer to be extended and a limiting amount of each short antisense primer that is complementary to and defines the 3' end of the long primer to be generated. The noncross-linking strand of the DNA probe was also generated by aPCR from the DNA sequence of interest. The long primers were annealed to the full-length noncross-linking DNA strand to form a partially double-stranded DNA. Cross-linking analogs and radioactive deoxyribonucleotides (dNTPs), followed by normal dNTPs, were enzymatically incorporated onto the long primers to form the double-stranded DNA cross-linking probes. This method is reproducible and avoids many of the difficulties encountered by other published methods.